2021
DOI: 10.1016/j.conbuildmat.2020.121725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature on the mechanical properties of basalt fibre self-compacting concrete as an overlay material

Abstract: The compressive strength of the basalt fibre SCC was diminished by 28% at 500°C. The splitting tensile strength of the SCC was increased by adding 0.25% of fibre. Considerable degradation in the flexural strength of fibrous SCC was seen at 300°C. Slant shear of hybrid concrete was highly affected by fibre content of overlay. Interfacial surface roughened by sand blast provided proper bond in hybrid sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Moreover, basalt fibers have shown remarkable resistance to elevated temperatures compared to other industrial fibers. Haido et al investigated the effect of basalt fibers on the workability of fresh self-compacting concrete [16], using J-ring flow and V-funnel flow. Experimental results showed that raising the temperature to 500 • C reduced the tensile and compressive strength of the self-compacting concrete by more than 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, basalt fibers have shown remarkable resistance to elevated temperatures compared to other industrial fibers. Haido et al investigated the effect of basalt fibers on the workability of fresh self-compacting concrete [16], using J-ring flow and V-funnel flow. Experimental results showed that raising the temperature to 500 • C reduced the tensile and compressive strength of the self-compacting concrete by more than 20%.…”
Section: Introductionmentioning
confidence: 99%
“…The modification effect of silane coupling agent KH550 (molecular formula C9H23O3NSi, 3-aminopropyltriethoxysilane, Guobang Chemical Co., Ltd. Jinan, China) is the best [ 30 ]. In this paper, KH550 was selected as the modifier for the surface treatment of BF, as showed in Figure 1 c. The performance indexes are presented in Table 4 .…”
Section: Raw Materialsmentioning
confidence: 99%
“…This numerical analysis was applied to BFRC beams with different fiber dosages and subjected to static loading at the whole range of applied load up to collapse. [ 29 , 30 ]. Basalt fiber is becoming more widely used in emulsified asphalt mixture [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Basalt fiber is an environmentally friendly and nonhazardous bio-based material that has high tensile strength and high temperature resistance, so it has been widely used in various construction projects [25]. In 2021, Haido et al found that the splitting tensile strength of self-compacting concrete was increased by adding 0.25% of basalt fiber [26]. In 2020, Mohammadyan-Yasouj et al found that basalt fiber and alginate were effective at stopping the strength reduction in cement concrete under raised temperatures [27].…”
Section: Introductionmentioning
confidence: 99%